Pelatihan Pernapasan dengan Zikir untuk Menurunkan Kecemasan pada Lansia di Posyandu Lansia Padukuhan Kenalan Bangunjiwo - Utami, Dinar Dewi; Ramadhan, Cahyo Setiadi (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2025)
Elderly is a stage of human development. Elderly or commonly known as old age is a condition that is impossible to avoid and is one of the developmental stages of the human life span. The elderly will encounter problems and anxiety is what they generally experience. Dhikr can increase self-confidence and increase hope in a person because it is closely related to religious and spiritual aspects. This study tested breathing training with dhikr to reduce anxiety in the elderly. The research used an experimental test with a quasi-experimental approach with pretest & posttest control group design. This study aims to determine the use of dhikr in breathing as a therapy to reduce anxiety in the elderly. The population was 87 elderlies with a sample of 20 people divided into the intervention and control groups. The anxiety score measurement was done using HARS (Hamilton Anxiety Rating Scale). The results of the Wilcoxon test showed that there was a significant difference in the intervention group of 0.004 (p<0.05). Thus, breathing training with dhikr is effective for reducing anxiety in the elderly.